Synthesis of HFC-134a by isomerization and hydrogenation - Suh, DJ; Park, TJ; Lee, BG; Park, KY (KOREAN INST CHEM ENGINEERS, 1996)
For the preparation of HFC-134a, the isomerization of CFC-114 and the hydrogenation of CFC-114a were investigated. Both reactions were catalyzed by AlCl3 and supported Pd catalysts, respectively. For the comparison purpose, the isomerization of CFC-113 was carried out also. With virgin AlCl3 catalyst, both isomerization reactions proceeded after a certain induction period probably because the catalyst needed the activation by the halogen exchange. The catalyst deactivated gradually with the time on stream. However, the deactivation rate could be reduced by removing impurities from the reactants. Isomerization rate of CFC-114 was much slower than that of CFC-113. Palladium supported on carbon catalyzed the hydrogenation reaction quite selectively while the selectivity declined when the support was replaced with different supports. The catalytic activity and selectivity to desired products increased in the following order. Pd/kieselguhr<Pd/silica-alumina congruent to Pd/silica gel<Pd/TiO2<Pd/Al2O3<Pd/C